Validation of a Driving Simulator Study on Driver Behavior at Passive Rail Level Crossings. (September 2018) - Larue, Grégoire S.; Wullems, Christian; Sheldrake, Michelle; Rakotonirainy, Andry
Objective: The behavioral validation of an advanced driving simulator for its use in evaluating passive level crossing countermeasures was performed for stopping compliance and speed profile. Background: Despite the fact that most research on emerging interventions for improving level crossing safety is conducted in a driving simulator, no study has validated the use of a simulator for this type of research. Method: We monitored driver behavior at a selected passive level crossing in the Brisbane region in Australia for 3 months ( N = 916). The level crossing was then replicated in an advanced driving simulator, and we familiarized participant drivers ( N = 54) with traversing this crossing, characterized by low road and rail traffic. Results: We established relative validity for the stopping compliance and the approach speed. Conclusion: This validation study suggests that driving simulators are an appropriate tool to study the effects of interventions at passive level crossing with low road and rail traffic, which are prone to reduced compliance due to familiarity. Application: This study also provides support for the findings of previous driving simulator studies conducted to evaluate compliance and approach speeds of passive level crossings.